ANALISIS PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSETS, DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR FARMASI DI BEI - Risal; Yudistari, Yola; Mayasafitri, Rina (Jurnal Akuntansi, Auditing dan Investasi, 2022)
This study was conducted to analyze the effect of variable Debt to Equity Ratio (DER), Return OnAsset (ROA), and Earning per Share (EPS) on stock prices in pharmaceutical sector companieslisted on Indonesian Stock Exchange. The sampling technique used is purposive sampling and thenumber of samples used is 32 companies. The variables used in this study are Debt to Equity Ratio(DER), Return on Assets (ROA), and Earning per Share (EPS) as independent variables and stockprice as the dependent variable. The results of this study indicate that Return on Assets (ROA) and Earning per Share (EPS) have a significant effect on stock prices, while the Debt to Equity Ratio (DER) has no significant effect on stock prices. However, simultaneously Debt to Equity Ratio (DER), Return on Assets (ROA), and Earning per Share (EPS) have a significant effect on stock prices.